Penerapan Metode Diskusi terhadap Peningkatan Keterampilan Berbicara Siswa Sekolah Menengah Pertama - Fitria, Sumratul; Huda, Mictahul; Yasinta, Iin Nur (Nuances of Indonesian Language, 2022)
This study aims to analyze the effect of discussion methods on improving students' speaking skills at the secondary school level. Speaking skills are one of the important aspects in language learning that can affect students' communication skills. The discussion method was chosen because it can create an interactive and collaborative learning atmosphere, where students can exchange ideas and opinions. This study uses a qualitative approach with data collection techniques through structured interviews with teachers and direct observation in the classroom. The results of the study showed that the application of the discussion method significantly improved students' speaking skills, as indicated by increased self-confidence and students' ability to express opinions verbally. In addition, students involved in the discussion showed an increase in vocabulary mastery and listening skills. This study also identified several factors that influenced the success of the discussion method, such as support from teachers, collaboration with parents, and the use of technology in learning. Thus, this study concludes that the discussion method is an effective strategy to improve students' speaking skills, and it is recommended that teachers integrate this method into the learning process to achieve better results in language mastery. The results of this study are expected to contribute to the development of language teaching methods in schools.